PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI DI SMAS YLPI PEKANBARU - Jasid Dendi; Suarman Suarman; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was aimed at finding out the effect of teacher personality on the students’ result of learning at SMA YLPI Pekanbaru. Population in this study are all the second grade students of SMA YLPI pekanbaru which are 75 students and this study used census sample technique. The data was collected by using quistionnaire about teacher personality that was distributed to respondent. To obtain the value of teacher personality, data analysis that is used is simple liniear regression analysis. Based on the results of the study, it can be known that there is an effect of the teacher personality on the result of learning of the second grade students of SMA YLPI Pekanbaru in Economic subject that is equal to 0.167% or 16.7%, while the rest of 83.3% is influenced by other factors that are not examined in this study, such as intellegence, peers, learning motivation, and learning discipline factor. It is expected that teachers will increase their personal comptence and students also study harder without seeing who their teacher is.Key Words: Teachers' Personality Competence, Students' Ability, Economic Learning